The information professionals in the Algarve region - Vargues, Maria Margarida; Matos, Gaspar; Salgado, Maria Armanda; Negrão, Sónia (Qualitative and Quantitative Methods in Libraries, 2019)
In this article it is presented the research carried out in the South of Portugal (region of Algarve) with the general objective to know the users perspective about the information services (public libraries and archives) and their professionals and afterwards define a marketing strategy to improve the image of these services. After the literature review it was decided to apply a questionnaire (quantitative approach) to the users and non-users of archives and libraries of the region. The data collected were analysed and although the perspectives of the users were very good there is the need to develop a marketing campaign to show the non-user the information services potentiality.